Evidence-based adverse effects of biologic agents in the treatment of moderate-to-severe psoriasis: Providing clarity to an opaque topic. (2nd November 2015) - Sorenson, Eric; Koo, John
Abstract: Background : Biologic agents have greatly enhanced the treatment of moderate-to-severe plaque psoriasis. Previous reviews of the safety of biologic agents have included patients with conditions other than psoriasis and/or have not used statistical significance as the primary analytic focus. Our aim was to review the current literature to identify significantly increased adverse events associated with the use of etanercept, adlimumab and ustekinumab for the treatment of moderate-to-severe plaque psoriasis. Methods : We performed a search of Ovid MEDLINE and the Cochrane Library to identify clinical trials, open-label extension studies and meta-analyses reporting statistical analysis of adverse events associated with the use of etanercept, adlimumab and ustekinumab for the treatment of moderate-to-severe plaque psoriasis. Results : We identified 17 clinical trials, 2 open-label extension studies and 8 meta-analyses. Adverse events reported to be significantly increased included squamous cell carcinoma (SCC), injection-site reaction, and headache associated with etanercept, overall nonmelanoma skin cancer (NMSC), SCC, and upper respiratory tract infection associated with adalimumab, and no significantly increased adverse events associated with ustekinumab. Conclusion : Current evidence suggests that when analyzed among patients with plaque psoriasis, few adverse effects of the biologic agents etanercept, adalimumab and ustekinumab have reached statistical significance. Further long-term studies conducting analysis of statistical significance should be performed.